Planar inverted-f antenna (PIFA): a study of specific absorption rate (SAR) by using dual frequencies in mobile communications - Sa’don, Siti Nor Hafizah (2013)
Planar inverted-F antenna formerly known as PIFA is a very low profile antenna, promising to be a very good candidate, less easily broken off, reduced power absorption by the head and less sensitive to the geometry of the structure. This type of antenna is mostly used in mobile phone today. By using CST Microwave Studio, PIFA is designed to analyse its performance and Specific Absorption Rate (SAR) with the COST244 spherical head model at different distances. The PIFA is operating at the frequency of 900 MHz and 1800 MHz which fulfilled the recent applications of Global System for Mobile Communications (GSM) and Universal Mobile Telecommunications System (UMTS). The SAR simulation is specified at 1 g and 10 g.